Backward logistic regression analysis of the determinants of the hand function among patients with leprosy: A cross-sectional study - Rizky Kusuma Wardhani; Melinda Harini; Fitri Anestherita (Malaysian Family Physician, 2024)
Introduction: The hands are the most common site of disability in leprosy. Hand dysfunction could result in difficulty performing activities of daily living. Therefore, hand function should be regularly assessed to ensure that any decrease in hand function could be diagnosed earlier. Methods: This study included 110 patients with leprosy from Likupang and Lembata, Indonesia. Hand function was assessed using the modified Jebsen test to measure hand function respective of the dominance. The grip and pinch strength were used as objective measures of clinical arm function. The World Health Organization (WHO) hand disability grade were used to determine the degree of impairment. Other factors such as age, sex and the type of leprosy were also considered. All factors were analysed using backward logistic regression. Results: Among the 110 participants, a decrease in the dominant (48.2%) and non-dominant (50.9%) hand functions were found. Pinch strength (OR: 3.39; 95% CI: 1.13–10.19) and age (OR: 4.91; 95% CI: 1.72–14.03) were significantly associated with hand function irrespective of the dominance. Conversely, the WHO hand disability grade (OR: 2.97; 95% CI: 1.10–8.04) and type of leprosy (OR: 0.34; 95% CI: 0.12–0.97) were significantly associated with only function of the dominant hand. Conclusion: There is a significant association of age and pinch strength with hand function regardless of the hand dominance. In contrast, the WHO hand disability grade and type of leprosy are significantly associated with the function of the dominant hand only.